PEMBERIAN PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL PADA TANAMAN MENTIMUN (Cucumis sativus L.) - Paul Worek; Beatrix Doodoh; Sofia Demmassabu (Universitas Sam Ratulangi, 2018)
ABSTRACT This study aims to determine the effect of concentration of liquid organic fertilizer (POC) on growth and yield on cucumber plants. This research was carried out in the village of Kolongan Tetempangan, Kalawat District, North Minahasa Regency for 2 months from July to August 2018. This research was conducted using the Completely Randomized Design method, with five treatments and four replications, namely the concentration of liquid organic fertilizer: 0 ml POC /2l water (P0), 2 ml POC /2l water (P1), 4 ml POC /2l water (P2), 6 ml POC /2l water (P3) and 8 ml POC /2l water (P4). Observations were made on each plant with observational variables, namely plant height, number of leaves, flowering time, number of flowers, number of fruits, fruit length, fruit diameter and fruit weight. The results showed that the administration of liquid organic fertilizer G Tonik has not given a significant effect on the growth of cucumber plants, but it has an effect on the production of cucumber plants in this case the fruit weight. Keywords : concentration, liquid organic fertilizer (POC), growth, hybrid cucumber